A clinicopathological study on interface dermatitis - Batchu, Vaishnavi R.; Panthalla, Vijaya L.; Kumar, P. V. Kiran; Penchalaiah, K. (International Journal of Research in Dermatology, 2022)
Background: Diagnosis of skin disorders that exhibit interface dermatitis is challenging in few scenarios. Despite sincere efforts, clinical examination per se can help us reach a handsome of differential diagnosis but not a gunshot specific diagnosis. Dermatopathology acts as a saviour to clinicians in such cases. Though histopathology is the gold standard, still one cannot make a “specific” diagnosis by histopathology alone because many have overlapping features. Therefore, the present study aims at the importance of clinicopathological correlation. The objectives were to study the clinical and histopathological features of various dermatoses, which exhibit interface dermatitis histopathologically and estimate clinicopathological concordance. Methods: This was a cross-sectional study done on 50 patients attending outpatient department (OPD), with the lesions suggestive of dermatoses known to exhibit interface dermatitis histologically. Strobe guidelines were followed. After a thorough clinical examination, punch biopsies were done and observed microscopically to detect interface dermatitis, if present. Secondary pathological features were studied to assess clinicopathological concordance. Microsoft excel and statistical package for the social sciences (SPSS) 21.0 were used for data analysis. Results: 76.74% cases were cases of lichen planus and its variants. The most common clinical presentation was papules. Among microscopic features, predominant finding was basal cell vacuolar change in epidermis (97.70% cases). Clinicopathological concordance was seen in 43 cases (83%). 7 cases were diagnosed solely based on histological correlation. Conclusions: A myriad of dermatoses exhibit interface dermatitis as a primary pathological feature. Only an apt correlation of clinical features with secondary pathological features can lead to a specific diagnosis from a bunch of differential diagnoses.